Developmental patterns of doublecortin expression and white matter neuron density in the postnatal primate prefrontal cortex and schizophrenia. - Samantha J Fung (PLoS ONE, 2011)
Postnatal neurogenesis occurs in the subventricular zone and dentate gyrus, and evidence suggests that new neurons may be present in additional regions of the mature primate brain, including the prefrontal cortex (PFC). Addition of new neurons to the PFC implies local generation of neurons or migration from areas such as the subventricular zone. We examined the putative contribution of new, migrating neurons to postnatal cortical development by determining the density of neurons in white matter subjacent to the cortex and measuring expression of doublecortin (DCX), a microtubule-associated protein involved in neuronal migration, in humans and rhesus macaques. We found a striking decline in DCX expression (human and macaque) and density of white matter neurons (humans) during infancy, consistent with the arrival of new neurons in the early postnatal cortex. Considering the expansion of the brain during this time, the decline in white matter neuron density does not necessarily indicate reduced total numbers of white matter neurons in early postnatal life. Furthermore, numerous cells in the white matter and deep grey matter were positive for the migration-associated glycoprotein polysialiated-neuronal cell adhesion molecule and GAD65/67, suggesting that immature migrating neurons in the adult may be GABAergic. We also examined DCX mRNA in the PFC of adult schizophrenia patients (n = 37) and matched controls (n = 37) and did not find any difference in DCX mRNA expression. However, we report a negative correlation between DCX mRNA expression and white matter neuron density in adult schizophrenia patients, in contrast to a positive correlation in human development where DCX mRNA and white matter neuron density are higher earlier in life. Accumulation of neurons in the white matter in schizophrenia would be congruent with a negative correlation between DCX mRNA and white matter neuron density and support the hypothesis of a migration deficit in schizophrenia.